Pengaruh Pendidikan Dan Pelatihan Terhadap Kinerja Karyawan Dengan Reward Sebagai Variabel Moderasi (Studi Kasus Karyawan Pada PT.BPRS Aman Syariah Sekampung) - Dupri, Muhammad Demsi; Lelawati, Nina; Handayani, Siti (Jurnal Manajemen DIVERSIFIKASI, 2023)
This study aims to determine and explain the effect of education and training on employee performance by testing the moderating variable at PT BPRS Aman Syariah Sekampung. With the population conducted in the study as many as 36 people. Based on the results of the analysis conducted by researchers, it shows that education has a significant effect on employee performance, resulting in a coefficient of t-count value of (31.777) and a significance value of (0.000), training has no effect and is not significant on employee performance, resulting in a coefficient of t-count value of (-902) and a significance value of (0.373). Then the reward does not moderate the effect of education on employee performance, resulting in a significance value of (0.513). Reward also does not moderate the effect of training on employee performance, resulting in a significance value of (0.707).